Infection Control Strategies Between Knowledge and Practice: A Study in Hussein Medical City-Karbala - Saeed Al-Mafragy, Hussein (Kerbala Journal of Nursing and Health Sciences., 2025)
Background: Infection control strategies designed to prevent the spread of healthcare-associated infections can be grouped into two categories: vertical and horizontal. Vertical strategies focus on a single organism while horizontal strategies aim to control the spread of multiple organisms simultaneously. Objective: To assess nurse’s knowledge and practice of infection control strategies during work in primary health care. Methodology: A descriptive quantitative study design was conducted to assess knowledge and practice about infection control strategy among nursing staff in Imam Hussein Medical City. The study was initiated from the period of 8ht July (2024) to 19th September (2024). A non-probability (convenience sample) consists of thirty males and female from nursing staff. The data collected through the utilization of a questionnaire and, by an interviewing technique with the nurses. Content validity for the study instrument was determined by using the panel of experts to investigate the clarity, relevancy, and adequacy of the questionnaire to achieve the present study's objectives. The results: The study findings show the nursing staff have a prominent level of knowledge and practice about infection control strategies in Imam Hussein medical city. Conclusion: The conclusion of the study is that there is an elevated level of knowledge and practice between nursing staff in imam Hussien medical city Recommendation: researchers recommended in importance to assess nursing practice to prevent infection transmission between staff and patients.